1998
DOI: 10.1901/jaba.1998.31-417
|View full text |Cite
|
Sign up to set email alerts
|

Using Number Line Procedures and Peer Tutoring to Improve the Mathematics Computation of Low‐performing First Graders

Abstract: Recommendations for mathematics instruction frequently include the use of manipulatives as a critical component. There are few experimental analyses of teaching strategies involving the use of manipulatives (e.g., the number line). This investigation used a multiple baseline design across three groups of students to examine the effectiveness of an experimental procedure for improving low‐performing children's skills in solving missing addend arithmetic problems using the number line. To address concerns about … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
9
0
2

Year Published

2000
2000
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 26 publications
0
9
0
2
Order By: Relevance
“…Can instruction improve students’ ability to use the diagrams when solving algebraic story problems? Research in both mathematics education and cognitive development suggests that students need effective instruction in order to use any type of external representations correctly (Fueyo & Bushell, 1998;Sowell, 1989; Uttal, Scudder, & DeLoache, 1997). Brief instruction on the nature of the particular visual representation may not be sufficient (Rittle‐Johnson & Koedinger, 2001), but more effective representation‐specific instruction could be time consuming, and may not transfer to other novel representations that students encounter.…”
Section: Discussionmentioning
confidence: 99%
“…Can instruction improve students’ ability to use the diagrams when solving algebraic story problems? Research in both mathematics education and cognitive development suggests that students need effective instruction in order to use any type of external representations correctly (Fueyo & Bushell, 1998;Sowell, 1989; Uttal, Scudder, & DeLoache, 1997). Brief instruction on the nature of the particular visual representation may not be sufficient (Rittle‐Johnson & Koedinger, 2001), but more effective representation‐specific instruction could be time consuming, and may not transfer to other novel representations that students encounter.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, there is some evidence to suggest that the use of Algebra Tiles can help students understand variables and like terms (Confrey & Lanier, 1980;Kitt & Leitze, 1992; but see Askey, 1999); Belenky and Nokes (2009) also found that the use of manipulatives helped students correctly identify variables in algebraic word problems. As with all manipulatives, one issue is that teachers must take time to instruct students about the representations or manipulatives before they are used (Fueyo & Bushell, 1998;Uttal, Scudder, & DeLoache, 1997); if students are not adequately familiar with the materials, helpful tools can quickly become a hindrance (Booth & Koedinger, 2012). Classroom time constraints must be considered when interventions are developed; even concept-based interventions which do not require familiarization with alternative representations take time.…”
mentioning
confidence: 99%
“…Peer tutoring has been used to deliver instruction in a variety of areas, including academic, social, and behavioral skills (e.g., Anhalt, McNeil, & Bahl, 1998;Flood, Wilder, Flood, & Masuda, 2002;Fueyo & Bushell, 1998;Gumpel & Frank, 1999;Pigott, Fantuzzo, & Clement, 1986;Trovato & Bucher, 1980). The positive results demonstrated in the literature have clear implications for the use of peer tutoring to teach skills to children to prevent firearm injury.…”
mentioning
confidence: 99%